Planting uniformity performance of motor-driven maize precision seeding systems - Yang, Shuo; Zhai, Changyuan; Gao, Yuanyuan; Dou, Hanjie; Zhao, Xueguan; He, Yakai; Wang, Xiu (International Journal of Agricultural and Biological Engineering, 2022)
Low accuracy planting uniformity affects yield. Seed meter type and forward speed typically interfere with the planting uniformity accuracy of motor-driven seeding systems. Two types of maize precision planters equipped with motor-driven planting systems are investigated in this study to ascertain the rule of planting uniformity in both simulated and field speeds. The simulated speed increases from 5 to 12 km/h at a 1 km/h interval in a laboratory environment. The test results show that the quality of feed index (QTFI) of the two planters decreased by 16.79% and 9.88%. This is primarily attributed to the increase in the miss index (MISS) by 11.62% and 9.70%, respectively. The field speed was set to four levels from 5 to 12 km/h in a field environment. The plant spacing scatter distribution results were analyzed, and the results of the two planters indicated that the average positive difference of the two planters linearly increased with the forward speed, and the negative difference of the two planters did not exhibit a linear correlation. The number of positive moving average points was 2.49 times greater than that of the negative moving average points of the finger pick-up maize precision planter, and 4.49 times in the air-suction maize precision planter. The results indicated that the increase of the positive difference of plant spacing is the major effect factor in the field planting uniformity of the two motor-driven maize precision planters. In addition, the plant spacing corresponded to the distribution frequency of the two planters in field was close to the target seed spacing of 25 cm with a max coefficient of variation (CV) of 21.55% and 20.66%, respectively, and those plant spacing values corresponded to max distribution frequency of the two planters at the four level field speeds were (24.69±0.63) cm and (25.63±0.32) cm, respectively. However, the multiples index (MUL) changed randomly affected by the increasing speed. The research results provide a direction for the optimization design of motor-driven maize precision planters. Keywords: electric drive metering, planting uniformity, maize precision planting, quality evaluation DOI: 10.25165/j.ijabe.20221505.5911 Citation: Yang S, Zhai C Y, Gao Y Y, Dou H J, Zhao X G, He Y K, et al. Planting uniformity performance of motor-driven maize precision seeding systems. Int J Agric & Biol Eng, 2022; 15(5): 101–108.